A qualitative exploration of the COVID‐19 pandemic on health and nutrition behaviours during the first 1000 days in Sri Lanka - Teresa R. Schwendler; Upul Senarath; Hiranya Jayawickrama; Dhammica Rowel; Noor Kawmi; Safina Abdulloeva; Chithramalee De Silva; Stephen R. Kodish (Maternal and Child Nutrition)
Abstract This study sought to understand reported impacts of the COVID‐19 pandemic on maternal and child health and nutrition behaviours during the first 1000 days of life. This qualitative and participatory substudy was embedded within mixed methods formative research conducted during 2020–2022 across two urban, three rural and one estate sector site in Sri Lanka. Semi‐structured interviews among caregivers of children aged 6–23 months (n = 34), influencers of caregivers, such as health workers (n = 37), leaders (n = 10) and pregnant women (n = 20) were conducted. Participatory workshops (n = 14) triangulated interview findings. Interview data were analyzed to identify salient themes using Dedoose. Numerical data from voting conducted in workshops were summed and triangulated with interview data. Findings suggest that the COVID‐19 pandemic and imposed restrictions shaped maternal and child health and nutrition behaviours through a complex interplay of factors. Imposed restrictions and changes to the food system contributed to temporary unemployment for wage workers and reduced purchasing power to maintain food security for vulnerable households. While deciding whether to seek care, fears of infection prevented usual care‐seeking decisions. Also, reduced incomes and disrupted public transportation made transport to health care facilities for antenatal care services difficult. Once women reached facilities, medical services and quality of care were negatively impacted. Implementing expanded community‐based services during home visits focused on the first 1000 days and beyond was one effective strategy to maintain maternal and child health and nutrition during the early pandemic in Sri Lanka.